Capacitance and surface of carbons in supercapacitors. (October 2017) - Lobato, Belén; Suárez, Loreto; Guardia, Laura; Centeno, Teresa A.
Abstract: This research is focused in the missing link between the specific surface area of carbons surface and their electrochemical capacitance. Current protocols used for the characterization of carbons applied in supercapacitors electrodes induce inconsistencies in the values of the interfacial capacitance (in F m −2 ), which is hindering the optimization of supercapacitors. The constraints of both the physisorption of N2 at 77 K and the standard methods used for the isotherm analysis frequently lead to a misleading picture of the porosity. Moreover, the specific surface area of carbons loses their meaning when the supercapacitor operates with organic electrolytes and ionic liquids and the actual surface involved in charge storage has to be assessed by molecular probes suiting the critical dimensions of the ions. In the case of certain carbons such as graphene type-materials, the voltage-driven mechanism may facilitate the access of electrolyte ions to spaces between carbon layers, providing a larger area than that estimated by gas adsorption. Finally, the morphological and porous features of carbons can be extremely modified when they are processed in electrodes. Due to their impact, all these issues should not be neglected and the characterization protocols must be adapted for this specific application of carbons. Graphical abstract: